2015
DOI: 10.1080/19443927.2015.1027452
|View full text |Cite
|
Sign up to set email alerts
|

Creative adaptations: integrating Feldenkrais principles in contemporary dance technique to facilitate the transition into tertiary dance education

Abstract: As conservatoire-style dance teaching has traditionally utilised a hierarchical approach through which the student must conform to the ideal requirements of the conventional technique, current discourse is beginning to question how dance training can develop technical acuity without stifling students' ability to engage creatively. In recent years, there has been growing interest in the field of somatics and its relationship to tertiary dance training due to the understanding that this approach supports creativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 15 publications
0
7
0
1
Order By: Relevance
“…Several Australian-based dance companies offer contemporary dance that combines ballet and modern techniques (Roche & Huddy, 2015). In recent years, a desire for increased fitness has led to the introduction of fitness classes into modern dance practice.…”
Section: Discussionmentioning
confidence: 99%
“…Several Australian-based dance companies offer contemporary dance that combines ballet and modern techniques (Roche & Huddy, 2015). In recent years, a desire for increased fitness has led to the introduction of fitness classes into modern dance practice.…”
Section: Discussionmentioning
confidence: 99%
“…Card (2006) reviewed the Australian dance sector and identified that major tertiary institutions in Australia follow the practices and philosophies of USA's educational trends towards choreography and performance. However, it has been argued that there is a disconnection between tertiary training and Australian dance industry needs; therefore, individuals need to acquire adaptive performance skills to be able to operate in the dance sector in Australia (Roche & Huddy, 2015).…”
Section: The Influence Of Dance Teachers' Previous Experiences As Expmentioning
confidence: 99%
“…Training individuals in the acquisition of adaptive performance skills involves re-examining current tertiary dance training practices at different levels (e.g., technical, pedagogical, and philosophical) (Parviainen, 2003) to understand how dance training can be enhanced (Roche & Huddy, 2015). Since expert performers mainly follow a 'conservatoire-style' dance teaching approach emphasising technique and steps (Fortin, 1998;Warburton, 2008), privileging dance performance and choreography over teaching in tertiary institutions might have negative consequences for tertiary dance training because expert performers, as teachers, might not be knowledgeable about pedagogical theory sustaining effective teaching (Fortin, 1993;Musil, 2010).…”
Section: The Influence Of Dance Teachers' Previous Experiences As Expmentioning
confidence: 99%
See 2 more Smart Citations